High-energy synchrotron X-ray diffraction measurements of simple bending of pseudoelastic NiTi shape memory alloy wires. Issue 2 (23rd May 2016) - Zhang, Baozhuo; Young, Marcus L.
Abstract : Many technological applications of austenitic shape memory alloys (SMAs) involve cyclical mechanical loading and unloading in order to take advantage of pseudoelasticity. In this paper, we investigated the effect of mechanical bending of pseudoelastic NiTi SMA wires using high-energy synchrotron radiation X-ray diffraction (SR-XRD). Differential scanning calorimetry was performed to identify the phase transformation temperatures. Scanning electron microscopy images show that micro-cracks in compressive regions of the wire propagate with increasing bend angle, while tensile regions tend not to exhibit crack propagation. SR-XRD patterns were analyzed to study the phase transformation and investigate micromechanical properties. By observing the various diffraction peaks such as the austenite (200) and the martensite ( ${\bar 1}12$ ), ( ${\bar 1}03$ ), ( ${\bar 1}11$ ), and (101) planes, intensities and residual strain values exhibit strong anisotropy, depending upon whether the sample is in compression or tension during bending.